Alternative Design of Abutment Damage Management for Glendeng Bridge Tuban Regency - Ghazanfar, Alfanditya; Muntaha, Moh.; Machsus, Machsus (Transpublika Publisher, 2025)
This study aims to reconstruct the damage to the bridge abutment that occurred in 2020. The bridge abutment was modeled based on its actual conditions, followed by simulations under various scenarios. The research methods included collecting secondary and primary data, as well as computational modeling. Secondary data collected consisted of bridge design drawings, soil data, and river water level data for specific time periods. The next step was to model the bridge structure using Plaxis software. The analysis results indicate that the collapse of the bridge abutment in 2020 was likely caused by floodwater infiltration into the soil, followed by a rapid decrease in floodwater levels. Slope stability analysis using PLAXIS software for the 2020 damage yielded a minimum safety factor (SFmin) of 1.184. After the flood subsided during the operational load stage (LWL), the SFmin indicated